2002
DOI: 10.1002/ajmg.10695
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics and molecular genetics of ovarian cancer

Abstract: Genetic alterations identified in human ovarian tumors by conventional banding, fluorescence in situ hybridization, comparative genomic hybridization, chromosome microdissection, loss of heterozygosity, chromosome microcell-mediated chromosome transfer, and microarray gene expression analysis are summarized and correlated. The significance of these findings with respect to pathologic classification and clinical application are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…An investigation of 7 stage III ovarian serous cancers by comparative genomic hybridization (CGH) revealed chromosomal aberrations in six patients with certain repeated changes including increased copy numbers of 1q, 2p, 2q, 3q, 6q, 8q, and 12p, and loss of 18q and X [ 47 ]. CGH analysis of malignant peripheral primitive neuroectodermal ovarian tumors revealed different chromosomal abnormalities including loss of chromosomes 1p, 1q, 4q, 6p, 6q, 7q, 8q, 13q and 19q; as well as gain of 1q, 2p, 7p, 9q, 18q and Xq [ 48 - 50 ]. The use of CGH and tissue microarrays in ovarian carcinoma [ 51 ] showed a frequent chromosomal over presentation on 2q, 3q, 5p, 8q, 11q, 12p, 17q and chromosome 20 combined to an amplification of 59 different oncogenes loci.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of 7 stage III ovarian serous cancers by comparative genomic hybridization (CGH) revealed chromosomal aberrations in six patients with certain repeated changes including increased copy numbers of 1q, 2p, 2q, 3q, 6q, 8q, and 12p, and loss of 18q and X [ 47 ]. CGH analysis of malignant peripheral primitive neuroectodermal ovarian tumors revealed different chromosomal abnormalities including loss of chromosomes 1p, 1q, 4q, 6p, 6q, 7q, 8q, 13q and 19q; as well as gain of 1q, 2p, 7p, 9q, 18q and Xq [ 48 - 50 ]. The use of CGH and tissue microarrays in ovarian carcinoma [ 51 ] showed a frequent chromosomal over presentation on 2q, 3q, 5p, 8q, 11q, 12p, 17q and chromosome 20 combined to an amplification of 59 different oncogenes loci.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several types of genetic studies have been performed to understand the molecular pathways of ovarian carcinogenesis. [1][2][3][4][5] Approximately 5-10% of ovarian cancers are hereditary, and the remaining 90 -95% are sporadic. The majority of hereditary cancers occur in women with germline mutations of the BRCA1 or BRCA2 gene, whereas, in sporadic ovarian cancers, somatic mutations of the c-erbB-2, c-myc and K-ras oncogenes and of the p53 tumor-suppressor gene (TSG) have been frequently observed.…”
mentioning
confidence: 99%
“…The other is a nucleotide substitution, C9ϾG, detected in a cell line, SKOV3. This substitution was considered to be a somatic 4 Hypermethylated sites are underlined. Hypermethylation was determined when the percentages of methylation at CpG sites 10 and 11 were higher than 56.5% and 56.2%, respectively.…”
mentioning
confidence: 99%
“…CGH has a much lower resolution than FISH, usually 3–5 Mb. CGH and FISH studies on human ovarian tumour samples have revealed common amplifications at 20q, 3q, and 8q [5]. …”
Section: Q Gene Amplification and Ovarian Cancermentioning
confidence: 99%